O15 Concordance between the new SLE-DAS, DORIS and Doria remission criteria for SLE: are they different in a real-life clinical setting?. (23rd March 2020) - Assunção, Helena; Jesus, Diogo; Inês, Luís
Abstract : Background: Systemic Lupus Erythematosus Disease Activity Score (SLE-DAS), a new, continuous measure, presents improved sensitivity to change as compared to SLE Disease Activity Index (SLEDAI-2K). It comprises 17 items, including important manifestations absent in SLEDAI (hemolytic anemia, gastrointestinal and cardiopulmonary involvement). The Doria and DORIS clinical remission criteria are both based in SLEDAI. This study aims to compare the attainment of clinical remission defined by SLE-DAS, DORIS and Doria criteria in a real-life clinical setting. Methods: Cross-sectional study of all SLE patients fulfilling ACR'97 and/or SLICC'12 classification criteria followed at an academic lupus clinic from January to September 2019. Fulfillment of DORIS, Doria and SLE-DAS clinical remission status was verified for each patient. The SLE-DAS clinical remission criteria were defined as a score of 0 in all clinical items of SLE-DAS and prednisone dose of 0–5 mg/day. We compared the attainment of clinical remission for each patient according to the three definitions. Sensitivity, specificity, positive and negative predictive values of SLE-DAS remission for Doria and for DORIS remission were calculated. Results: The study population included 293 patients (female = 86.7%; mean age = 47.7 years; mean disease duration =14.4 years). The proportion of patients in clinical remission was 76.5% as defined by the DORIS and Doria criteria. Patients in clinical remission according to the SLE-DAS definition exactly matched those defined by either Doria or DORIS criteria and there were no discordant cases. From patients in clinical remission, 17%, 93.3%, and 30.4% were treated with prednisone, antimalarials, and immunosuppressants, respectively. Conclusions: In a real-life cohort of SLE patients, clinical remission is consistently defined by applying either SLE-DAS, DORIS or Doria criteria. SLE-DAS definition is more straightforward, as it does not require the PGA or additional manifestations not included in SLEDAI.